Women who die in custody: What Australian coroners' reports tell us. Issue 4 (13th October 2022) - Walsh, Tamara
Abstract: Women's deaths in custody remain under‐researched around the world. This article reports on a large‐scale study on deaths in custody conducted in Australia that involved an analysis of 736 coroners' inquest reports dated between 1991 and 2020. Women were substantially under‐represented among this sample, comprising less than 5% of all deaths, but half of the women were Indigenous. While most of the women had a range of individual risk factors in common – such as a history of victimisation, mental illness and drug and alcohol use – the Indigenous women also experienced systemic racism from their custodians and the medical personnel to whom they were referred for treatment. While most coroners focused primarily on the cause of death, some made recommendations directed at addressing unconscious bias. This research supports calls for alternatives to detention for women and the decriminalisation of racialised offences such as public intoxication.